Coupling flow with nutrient dynamics via BioChemFOAM in the Mississippi River. Issue 4 (2nd October 2018) - Hernandez Murcia, Oscar E.; Schnoebelen, Douglas J.; Papanicolaou, Athanasios N.; Abban, Benjamin
Abstract : An enhanced three-dimensional unsteady hydrodynamic, multispecies transport fate model called BioChemFOAM was developed in OpenFOAM-free computational fluid dynamic platform for understanding and predicting nutrient dynamics, namely, transport and transformation, in aquatic ecosystems. The study motivation was to better quantify transport and distribution of nutrient species in the Upper Mississippi River Basin (UMRB), a major source of nutrient contributor from intense agriculture. The study is unique in examining the transport and reactivity rates under complex hydrologic conditions where main conveyance channels and backwaters co-exist. The model has two main components: a new coupling of turbulent flow processes with multiple species to modulate transport and reaction rates simulations at channel/backwater areas and a complex chemical and biological transformation module suited for species reaction rates in backwaters. The coupled model was first tested for an idealistic domain/case borrowed from the literature. The final model was calibrated, tested and verified in the UMRB.